Peningkatan Kemampuan Bahasa Anak Usia 5-6 Tahun Melalui Permainan Pesan Berantai - Rizka Maharani; Lusi Marleni; Putri Asilestari (Jurnal Pendidikan Tuntas, 2025)
This research aims to determine the improvement in language skills of children aged 5-6 years, Adiba Islamic School Kindergarten, Rimbo Panjang Village, Tambang District. This research is motivated by the lack of variety in learning and there are still many children who have not been able to reach language proficiency indicators. This research is classroom action research (CAR) The subjects of this research were 15 children in the arrahim class at Adiba Islamic School Kindergarten, while the object of this research is chain message games and the development of language skills. This research was carried out in 2 cycles, each cycle holding 2 meetings. The data collection techniques used in this research are observation and documentation. Based on the results of research before the action, in the not yet developing category there were 7 children (46.6%), in the beginning to develop category there were 7 children (46.6%), in the developing according to expectations category there was 1 child (6.6%). In cycle II, children's language abilities experienced a significant increase. There are no more children in the underdeveloped category. 5 children (33.3%) were in the starting to develop category, 3 children (20%) were in the developing as expected category, and there were 7 children (46.6%) in the very well developing category. Thus, it can be concluded that the chain message game can improve the language skills of kindergarten children at Adiba Islamic School, Rimbo Panjang Village, Tambang District.